2010
DOI: 10.1016/j.brainresbull.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to parathion alters lipid metabolism in adulthood: Interactions with dietary fat intake and implications for neurodevelopmental deficits

Abstract: Organophosphates are developmental neurotoxicants but recent evidence also points to metabolic dysfunction. We determined whether neonatal parathion exposure in rats has long-term effects on regulation of adipokines and lipid peroxidation. We also assessed the interaction of these effects with increased fat intake. Rats were given parathion on postnatal days 1-4 using doses (0.1 or 0.2 mg/kg/ day) that straddle the threshold for barely detectable cholinesterase inhibition and the first signs of systemic toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…Perinatal and prenatal exposures have also been shown to result in excessive weight gain and adipose tissue mass in offspring (30, 31, 3847). Human studies have demonstrated a positive association between EDC exposures and obesity, increased weight circumference, or increased body mass index (28, 30, 40, 42, 4865). …”
Section: Adipogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Perinatal and prenatal exposures have also been shown to result in excessive weight gain and adipose tissue mass in offspring (30, 31, 3847). Human studies have demonstrated a positive association between EDC exposures and obesity, increased weight circumference, or increased body mass index (28, 30, 40, 42, 4865). …”
Section: Adipogenesismentioning
confidence: 99%
“…EDCs including diazinon, parathion, malathion, BPA, PCB-77, PCB-153, and PCB-180 increase the levels of pro-inflammatory cytokines, such as TNF-α and interleukin 6 in adipose tissue (34, 37, 48, 71, 74, 81, 84, 88, 130134). Together, these EDC effects induce a pro-inflammatory phenotype in adipose tissue.…”
Section: Pro-inflammatory Statementioning
confidence: 99%
See 1 more Smart Citation
“…At lower doses administered during development, chlorpyrifos also produces excess weight gain and dysregulation of leptin [11], along with a metabolic profile resembling prediabetes [24]. Similarly, when we exposed neonatal rats to parathion at doses straddling the threshold for barely-detectable cholinesterase inhibition, we found later emergence of a prediabetes-like state, involving excessive weight gain, hyperglycemia, abnormalities of lipid metabolism and adipose tissue inflammation [12,13]. Further, many of the metabolic effects of early-life OP exposure were exacerbated when animals were switched to a high-fat diet in adulthood, including a much greater fat-induced weight gain than that with the equivalent dietary change in controls [12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate exposure may contribute to diabetes via disruption of adipokine signalling and metabolic regulation 14. Recent experimental studies have demonstrated excess weight gain, hyperlipidaemia and hyperinsulinaemia persisting into adulthood in rats exposed neonatally to the organophosphate chlorpyrifos; the magnitude of these effects differs between males and females 15 16.…”
mentioning
confidence: 99%